Djurägarens upplevelse av djursjukskötarens bemötande vid besöket på kliniken - Hillgren, Emma (2012)
Veterinary medicine is not merely an area of occupation but also an area of business. In a business the customer service is its identity and brand and more importantly what makes the client choose and recommend the clinic to other potential customers. The licensed veterinary nurse is habitually the one who first meets the clients at the clinic. Therefore it is particularly important for the licensed veterinary nurse at the clinic to offer high-quality customer service.